East Asian winter monsoon and Arctic Oscillation - Gong, DY; Wang, SW; Zhu, JH (Geophysical Research Letters, 2001)
In this study, the connection between Arctic Oscillation (AO) and variability of East Asian winter monsoon is investigated. Two indices are chosen to describe the winter monsoon. One is the intensity of the Siberian High, defined as the average SLP over the center region, and the other is the temperature of eastern China, averaged over 76 surface stations. These are two tightly related components, correlate at -0.62 for period 1951-99. Temperature drops by 0.64 degrees Celsius in association with a one standard deviation increase in Siberian High intensity. It is found that there are significant out-of-phase relationships between the AO and the East Asian winter monsoon. The correlation coefficient between the AO and the Siberian High intensity index is -0.48 for period 1958-98. AO is also significantly correlated with the temperature of eastern China at 0.34. However, when the linear trend is removed, the correlation between AO and temperature is no longer significant. But the strong connection between the AO and Siberian High, and between the Siberian High and temperature are still significant. These results reveal that the AO influences the East Asian winter monsoon through the impact on the Siberian High. Negative phase of the AO is concurrent with a stronger East Asian Trough and an anomalous anticyclonic flow over Urals at the middle troposphere (500hPa); Both the AO and the Eurasian pattern play important roles in changes of the Siberian High and/or East Asian winter monsoon. They account for 13.0% and 36.0% of the variance in the Siberian High respectively. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000168617900045&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Geosciences, Multidisciplinary SCI(E) 255 ARTICLE 10 2073-2076 28